2019
DOI: 10.2471/blt.19.229773
|View full text |Cite
|
Sign up to set email alerts
|

Trends and regional distribution of outpatient claims for asthma, 2009–2016, Germany

Abstract: ObjectiveTo investigate asthma morbidity in Germany by calculating current prevalence, examining its temporal and spatial trends and estimating the total number of asthmatics in Germany and calculating age-, sex- and residence-specific risk.MethodsWe used claims data reported by physicians during 2009–2016, including outpatient diagnoses of all statutory health insured individuals, comprising 85.3% (70 416 019/82 521 653) of the total population in Germany in 2016. We performed a spatial analysis of asthma pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Case ascertainment and prevalence estimation. We defined a patient with concurrent diagnoses, when each ICD-10 codes J44 'other chronic obstructive pulmonary disease' 36,37 and J45 'asthma' 21,31 were diagnosed in at least two different quarters in 2017, resulting in total of four diagnoses (i.e., two diagnoses of asthma in two different quarters and two COPD diagnoses in two different quarters). In addition, all diagnoses should have a diagnostic modifier "confirmed diagnosis" in contrast to 'suspected disease' or 'cured disease' .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case ascertainment and prevalence estimation. We defined a patient with concurrent diagnoses, when each ICD-10 codes J44 'other chronic obstructive pulmonary disease' 36,37 and J45 'asthma' 21,31 were diagnosed in at least two different quarters in 2017, resulting in total of four diagnoses (i.e., two diagnoses of asthma in two different quarters and two COPD diagnoses in two different quarters). In addition, all diagnoses should have a diagnostic modifier "confirmed diagnosis" in contrast to 'suspected disease' or 'cured disease' .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, claims data are primarily collected for reimbursement purposes and not for morbidity estimation and are known to overestimate the true epidemiological prevalence, in particular, if a case definition is only based on a single diagnosis. Previous research on asthma and COPD based on routine data thus applies a more conservative case definition 21,22,[31][32][33] . Furthermore, per case definition (i.e., diagnoses in at least two different quarters), patients with concurrent asthma/COPD diagnoses have higher rates of health care contacts, in particular, if patients visit different physicians as compared to controls.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In an earlier study, we have reported a noticeable variation in the prevalence of asthma on district level. 10 Furthermore, local spatial clusters were present with an increased prevalence in Lower Saxony, North Rhine-Westphalia, Schleswig-Holstein and Thuringia. 10 The risk of developing asthma was also higher in urban as compared to rural regions.…”
Section: Introductionmentioning
confidence: 98%
“… 10 Furthermore, local spatial clusters were present with an increased prevalence in Lower Saxony, North Rhine-Westphalia, Schleswig-Holstein and Thuringia. 10 The risk of developing asthma was also higher in urban as compared to rural regions. 10 Urban–rural differences of allergic diseases have also been reported in international studies.…”
Section: Introductionmentioning
confidence: 98%
“…Asthma is still one of the most common respiratory diseases [1,2], with 262 to 340 million cases worldwide, including 800,000 affected children living in Germany and a region-dependent incidence [3][4][5][6][7][8] associated with a high number of undiagnosed cases [9][10][11][12]. Based on the German national guidelines, the NVL Asthma 2020 (=Nationale Versorgungsleitlinie Asthma 2020), severe asthma exacerbation is defined by tachypnea, tachycardia, peak expiratory flow variations, reduced oxygen saturation, or speech dyspnea [13].…”
Section: Introductionmentioning
confidence: 99%